A Case of Myoepithelial Hamartoma: Morphological Variation Supported by OCT4 Expression - Takehiro Tanaka; Kenji Nishida; Masaya Iwamuro; Satoru Kikuchi; Tadashi Yoshino (Case Reports in Gastrointestinal Medicine)
In this report, we describe a patient with myoepithelial hamartoma, which is regarded as synonymous with adenomyosis and heterotopic pancreas. Endoscopy revealed a submucosal tumor in the antrum of the stomach. Subsequently, distal gastrectomy with Roux-en-Y reconstruction was performed. Histological findings of adenomyomatous lesion and heterotopic pancreatic tissue were observed in this lesion. The distribution of OCT4, which is a pluripotency marker, varied in each part.